2022
DOI: 10.3389/fpsyg.2022.951931
|View full text |Cite
|
Sign up to set email alerts
|

Have you “involution” today—Competition psychology scale for college students

Abstract: In order to investigate the competitive psychology of college students in the current context of fierce social competition, this study compiled a competition psychology scale for college students [i.e., the Competition Psychology Scale for College Students (CPS-CS)]. The scale was administered online to 628 university students in different regions of China. After item analysis, reliability analysis, and validity analysis, a 6-item scale was finally formed. CPS-CS contains four dimensions: hypercompetitive atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…We found that some proactive students took initiative to make competition with their counterparts in a role of “involutioner” (an anxiety maker) rather than “involutionee” (an anxiety sufferer). This is in line with Liu et al's (2022) HCA. Therefore, future studies can conduct a mixed approach combing the scale measurement and deep interview to access the involutional psychology of college students.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that some proactive students took initiative to make competition with their counterparts in a role of “involutioner” (an anxiety maker) rather than “involutionee” (an anxiety sufferer). This is in line with Liu et al's (2022) HCA. Therefore, future studies can conduct a mixed approach combing the scale measurement and deep interview to access the involutional psychology of college students.…”
Section: Discussionsupporting
confidence: 92%
“…In consonance with Liu et al's (2022) involutional representations, three constructs concerning the Chinese college students' involutional behavior repeatedly emerge in literature: (1) Academic Behavior , such as competing for a high score or scholarship. Instead of stimulating academic prosperity, the overdue academic involution may not only put students under constant pressure and distress, fearing that they will not be able to obtain a desirable score, a scholarship and even graduation, but also catalyze the unethical behaviors such as the falsified data, plagiarism, ghostwriting, and other off‐beat behaviors (Li, 2023, p. 2).…”
Section: Literature Reviewmentioning
confidence: 70%
See 3 more Smart Citations